Situation analysis of Rubyiro Sub-catchment of the Rusizi River in Rwanda - Uwanyirigira, D.; Musana, B.; Atampugre, Gerald; Tilahun, Seifu A.; Oke, Adebayo; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
The increasing pressures on socio-ecological landscapes (SEL) in developing countries, including Rwanda, stem from a complex interplay of factors, primarily driven by heightened demand for essential livelihood assets. These assets encompass access to food, health services, water, forest resources, housing, and agricultural spaces. In Rwanda, the excessive and often mismanaged utilization of productive landscape resources is evident, exacerbated by climate change and lapses in institutional policies. This situation has led to diminishing biodiversity and ecosystem services, threatening the sustainability of agricultural production systems and other livelihoods within the country.